Sagina nilagirica (Sagineae, Caryophyllaceae), a new species from Nilgiri Biosphere Reserve (Western Ghats, India) - Athira, Subramanian; Kanakambika, Govindan; Smitha, Manikandan; Remya, Sivakumaran; Muhsina, Abdul Azeez; Maya, Chandrasekharan Nair (Phytotaxa, 2024)
Sagina nilagirica is described and illustrated as a new species from Doddabetta hills of Nilgiri Biosphere Reserve (Tamil Nadu, India). It is morphologically similar to S. procumbens by its habit (ascending to decumbent), linear leaves, tetramerous flowers and ovoid, 4-valved capsule, but differs in having non-succulent leaves, by the absence of persistent basal leaves, upright fruiting pedicel, lanceolate and pubescent sepal, trigonal petals with bilobed limb and crassuloid-type seeds with reniform, smooth, non-grooved seed surface having distinct elongate cog-wheel like epidermal cells with acute interdigitating teeth.